Irradiated Single Crystal Chemical Vapor Deposition Diamond Characterized with Various Ionizing Particles. Issue 21 (8th August 2019) - Naaranoja, Tiina; Golovleva, Maria; Gädda, Akiko; Martikainen, Laura; Ott, Jennifer; Berretti, Mirko; Garcia, Francisco; Luukka, Panja; Tuuva, Tuure; Österberg, Kenneth
Abstract : The radiation hardness of diamond at the sensor level is studied by irradiating five sensors and studying them with various particle sources, without making any modifications to the sensors in between. The electronics used in the characterization is not irradiated to ensure that any observed effect is merely due to the sensor. Three sensors have received a fluence of 10 14  protons cm −2 and two 5⋅10 15  protons cm −2 . At the lower fluence, the impact on the charge collection efficiency is very small, when the applied bias voltage is above 1 V μm −1 . For the higher fluence, the charge collection efficiency is lower than expected based on earlier studies of diamond radiation hardness on the substrate level. Furthermore, it is noticed that the irradiation has a stronger impact on the signal amplitude recorded with a fast timing than with a charge sensitive amplifier. Abstract : The radiation hardness of synthetic single crystal diamond sensors is studied via irradiation experiments with 24 GeV protons. Such sensors are used in particle physics experiments for precise proton time‐of‐flight measurement. The electrodes and interfaces are found to suffer significantly from the radiation in comparison with the diamond crystal, when the results are compared with those in previous radiation hardness studies.